PERANCANGAN SISTEM POINTING ANTENA TOWER BTS OTOMATIS UNTUK KOMUNIKASI WI-FI BERBASIS APLIKASI ANDROID: RANCANG BANGUN APLIKASI KONTROL POINTING ANTENA BTS BERBASIS ANDROID - Fadhilah, Naufal; Rafsyam, Yenniwarti (Spektral, 2024)
In this digital era, the demand for reliable and efficient communication networks is increasingly rising. One of the critical components in communication networks is the Base Transceiver Station (BTS), which requires an antenna with optimal orientation to ensure maximum signal quality. This research aims to design an automatic BTS antenna pointing system using an Android application. The system utilizes DC Gear Motors and Servo Motors to adjust the antenna's position and orientation in real-time. The Android application serves as an intuitive user interface, allowing technicians to easily calibrate and adjust the antenna. The system is designed to enhance time efficiency and accuracy in the antenna pointing process. The application is developed using Android Studio and Firebase Realtime Database. It is connected to the ESP32 via mobile Wi-Fi internet. The developed application functions effectively, enabling the tower to rotate to the specified angle accurately as commanded by the application. The code and system built significantly assist technicians in the antenna pointing process.